Synthesis and Crystal Structure of TeBr2IBr - Soleimani, Esmaiel; Mitu, Liviu (Asian Journal of Chemistry, 2011)
The reaction of a mixture of Te, TeBr4 and I2 in molar ratios of 1:3:2 in a sealed evacuated ampoule at a temperature gradient range from 200ºC to 180 ºC yielded red crystals. The single crystal X-ray data for this compound showed that it had the TeBr2IBr structure. In this compound, IBr is bonded to TeBr2 and Br-I-Te has a nearly linear skeleton. The compound crystallizes in monoclinic system with a space group of P21/c and the lattice constants a = 16.234(2) Å, b = 11.082(4) Å, c = 15.147(3) Å, a = 90.03(1)º, b = 98.58(4)º, g = 90.06(2)º.